Anthocyanin incorporated dental copolymer: bacterial growth inhibition, mechanical properties, and compound release rates and stability by (1)h NMR - Hrynash, Halyna; Pilly, Vinay Kumar; Mankovskaia, Alexandra; Xiong, Yaoyang; Nogueira Filho, Getulio; Bresciani, Eduardo [UNESP]; Lévesque, Céline Marie; Prakki, Anuradha (International Journal Of Dentistry, 2014)
Objective. To evaluate bacterial growth inhibition, mechanical properties, and compound release rate and stability of copolymers incorporated with anthocyanin (ACY; Vaccinium macrocarpon). Methods. Resin samples were prepared (Bis-GMA/TEGDMA at 70/30 mol%) and incorporated with 2 w/w% of either ACY or chlorhexidine (CHX), except for the control group. Samples were individually immersed in a bacterial culture (Streptococcus mutans) for 24 h. Cell viability (n = 3) was assessed by counting the number of colony forming units on replica agar plates. Flexural strength (FS) and elastic modulus (E) were tested on a universal testing machine (n = 8). Compound release and chemical stability were evaluated by UV spectrophotometry and (1)H NMR (n = 3). Data were analyzed by one-way ANOVA and Tukey's test ( α = 0.05). Results. Both compounds inhibited S. mutans growth, with CHX being most effective (P < 0.05). Control resin had the lowest FS and E values, followed by ACY and CHX, with statistical difference between control and CHX groups for both mechanical properties (P < 0.05). The 24 h compound release rates were ACY: 1.33 μg/mL and CHX: 1.92 μg/mL. (1)H NMR spectra suggests that both compounds remained stable after being released in water. Conclusion. The present findings indicate that anthocyanins might be used as a natural antibacterial agent in resin based materials.